2014
DOI: 10.15314/tjse.201428100
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between physical activity and healthy quality of life in students

Abstract: The purpose of this research is to relationship between physical activity and healthy quality of life in students. Statistical population of this research involves all physically active male students in Iran from which 1352 students participated in the study as sample by using cluster sampling and sample random method. Collection data tools of this research were questionnaire according to its nature: Sharkey Physical Activity Questionnaire and Life Quality Questionnaire (WHOQOL-BREF, 2204) were used after cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Sited in the present study as a consequence to body gain relative to health and fitness. Reported in a similar study as a model of an inactive lifestyle and their costs [37]. The case of our leavers recommended considering a sport and physical activity as a part of their daily lifestyle.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Sited in the present study as a consequence to body gain relative to health and fitness. Reported in a similar study as a model of an inactive lifestyle and their costs [37]. The case of our leavers recommended considering a sport and physical activity as a part of their daily lifestyle.…”
Section: Resultsmentioning
confidence: 86%
“…The case of this study that confesses the benefits of school time structure activities in the increases of health-related fitness. Showing in previous among the benefits of PA via its influence on the levels of physical activity as well as their positive impact on health quality of life in adolescence or adulthood [37].…”
Section: Resultsmentioning
confidence: 99%
“…Past studies have shown a positive relationship between physical activeness and QoL (Grant et al, 2009; Kokandi et al, 2019). It has been suggested that physical fitness can affect the brain functioning, emotional regulation, physical conditioning, and psychological well-being of a person (Talebpour et al, 2014). A study on Malaysian children reported a strong positive correlation between physical activeness (specifically moderate to vigorous exercise) and QoL (Wafa et al, 2016).…”
mentioning
confidence: 99%
“…A study on Malaysian children reported a strong positive correlation between physical activeness (specifically moderate to vigorous exercise) and QoL (Wafa et al, 2016). Furthermore, PA plays an important role in reducing mental pressure or stress accumulated throughout daily activities nowadays, and positively correlated with both physical and mental QoL in college students (Talebpour et al, 2014). Individuals who are physically inactive had a higher level of declines in physical performance and at a higher risk of premature death (Klein et al, 2018).…”
mentioning
confidence: 99%
“…Based on previous studies, regular exercise has a great role in enhancing the QOL (Alkhamis et al, 2021). Recent papers were published in Iran (Talebpour et al, 2014), UK (Rodríguez-Fernández et al, 2017) and Brazil (Peleias et al, 2017) respectively showed that there is a significant association between PE and QOL. None of the previous published papers focused on the impact of a specific type of physical exercise on a definitive dimension of QOL.…”
mentioning
confidence: 99%